Propuesta de rediseño de la línea de producción en carrocerías DAVMOTOR. CIA. LTDA. Para el mejoramiento de la productividad. - Ochoa Sangacha, Andrés Gustavo (2020)
This project was developed in the Ecuadorian company Davmotor. Cía.Ltda located in Ambato Province of Tungurahua in the Cunchibamba neighborhood, dedicated to the manufacture of bodyworks nationwide, currently the company causes dissatisfaction in its customers, because operators do not have a properly distributed workload, there is a considerable risk of delays in the development and delivery of the units; whereby, the objective of the investigation of this work is to propose a redesign in the three-door bus body production line to increase the productivity of annual units, starting with the formulation of the hypothesis applying the inductive method which will be through the diagnosis of the current situation through observation in the Company, identifying difficulties that arise in order to solve them; initially it was done a tour of the facilities to get used to the production processes and their work stations, that integrate the procedures for the construction of the bodywork, formalizing reference methods with cycle times per actual units in minutes in their manufacture and the different supplements per workload, that allows technically to identify the existence of the bottleneck or capacity restriction in the production line; with the result of this investigation, the current work stations in one unit and the redistribution of operators were reduced, reaching to reduce the standard time by 1% per unit manufactured, the efficiency of the line was increased by 7% and a productivity of 21 units per year was achieved, minimizing delays in the production process and adapting to the annual demand established by the market, in this way, the penalty costs for late deliveries were minimized and the annual net profit increased by 15%.